POU6F2 mutation in humans with pubertal failure alters GnRH transcript expression - Cho, Hyun-Ju; Gurbuz, Fatih; Stamou, Maria; Kotan, Leman Damla; Farmer, Stephen Matthew; Can, Sule; Tompkins, Miranda Faith; Mammadova, Jamala; Altincik, S. Ayca; Gokce, Cumali; Catli, Gonul; Bugrul, Fuat; et al. (Frontiers in Endocrinology, 2023)
Impaired function of gonadotropin-releasing hormone (GnRH) neurons can cause a phenotypic spectrum ranging from delayed puberty to isolated hypogonadotropic hypogonadism (IHH). It is critical to understand the development and regulation of these neurons for therapeutical treatment.Here, we identified a mutation in the POU6f2 transcription factor associated with IHH and show that POU6F2 isoform1 can regulate GnRH transcription. This is the first study to show a function of POU6f2 isoform1 and identifies a mutation in a IHH patient that alters its function.